Pengolahan Sampah Plastik Menjadi Bahan Kreasi Bernilai Ekonomi - Wiji Syahfitri; Ryan Pramana; Wafiq Ariska; Anisa Niwanda; Meilinda Suriani Harefa (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Plastic remains dominant in everyday life in Indonesia, favored for its affordability and long-lasting properties. However, the negative impact is seen through non-biodegradable plastic waste which damages the environment and causes the transfer of toxic compounds. Various efforts to deal with plastic waste, such as burning and burial, produce new problems. The lack of public knowledge and awareness highlights the importance of education in managing plastic waste. This research aims to reveal the situation of plastic waste processing, with a theoretical review of previous research, literature study methodology, and the potential for creativity in managing plastic waste. The research method uses literature study and observation techniques to collect information. The result of this research is a product created with economic value from plastic waste. Apart from reducing plastic waste, these creative products can also increase people's income, because the products produced can be sold at high prices.